PERAN KEPEMIMPINAN DALAM BIROKRASI PEMERINTAHAN DI INSTITUT PEMERINTAHAN DALAM NEGERI KAMPUS SULAWESI SELATAN - Arnas Arnas (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2022)
This study aims to determine the role of leadership in the government bureaucracy at the Institute ofDomestic Administration, South Sulawesi Campus. The type of research used is qualitative, which is a formof research that aims to provide an overview as the kind of data collected objectively from the field withthe phenomenological type. Data collection techniques used were observation, interviews with a number ofinformants. Data analysis using an interactive analysis model. The results showed that the role of leadershipin the government bureaucracy at the Institute of Internal Administration, South Sulawesi Campus has notbeen fully implemented optimally. Organization, Evaluation, and Initation have not been implemented well.Inhibiting Factors The role of leadership, namely the Position Factor, which indicates the incumbent and thesituation and condition factors, the Director must be able to have high flexibility in the situation and conditionsfor employees.